2003
DOI: 10.1103/physrevb.68.014406
|View full text |Cite
|
Sign up to set email alerts
|

Effects of disorder on the dynamics of theXYchain

Abstract: We investigate the effects of disorder on the dynamics of the sϭ1/2 XY model in one dimension. The energy couplings are randomly drawn independently from a bimodal distribution. We use an extension of the method of recurrence relations, in which an averaging over realizations of disorder is incorporated into the definition of the scalar product of the dynamical Hilbert space of j z (t), to determine analytically the first six basis vectors as well as the corresponding recurrants. We then use an ansatz for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 39 publications
1
17
0
1
Order By: Relevance
“…Introducing extra operators B iσ , the correlation functions of the form A n B iσ can be calculated by using Eqs. (9) and (24). In Refs.…”
Section: General Formulationmentioning
confidence: 99%
“…Introducing extra operators B iσ , the correlation functions of the form A n B iσ can be calculated by using Eqs. (9) and (24). In Refs.…”
Section: General Formulationmentioning
confidence: 99%
“…For reviews, see [3][4][5][6][7]. For a partial list of recent papers, see [8][9][10][11][12][13][14][15][16][17][18][19][20][21].…”
Section: Introductionunclassified
“…Given the zeros of Q N , it is now straightforward to obtain a 0 (t) by Equation (12). For example, if N = 6,…”
Section: A 0 (T) For Finite Nmentioning
confidence: 99%
“…Some exact results have been obtained for the one-dimensional (1-D) pure quantum spin models, e.g., the 1-D transverse Ising model and the 1-D XY model [4,5,6]. Recently, more attention has been paid to the investigation of the dynamical behavior of disordered systems [7,8,9,10,11,12], which can be applied to describe the properties of many materials such as window glass, magnets with frozen-in disorder, etc.. One simple but important example of such systems is the 1-D random transverse Ising model (RTIM).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we have investigated the effects of Gaussian disorder on the dynamics of the 1-D RTIM [12], and have found that there are two crossovers when the standard deviation of random variables is small and there is no crossover if the value of the standard deviation is large enough. Besides, the dynamical behavior of the random-bond transverse Ising model with four-spin interactions [13] and the disordered XY chain [9,10,11] have been studied.…”
Section: Introductionmentioning
confidence: 99%